PENDEKATAN ARSITEKTUR PERILAKU SEBAGAI DASAR PERTIMBANGAN FOKUS MASALAH DAN SOLUSI PADA RANCANGAN FASILITAS PUBLIC SPACE - Istifarila, P.L.; Prassetio, A.; Perbangsa, Y.; Ansani, J.N.; Prajnawrdhi, T.A. (Buletin Udayana Mengabdi, 2023)
Nyang Nyang Beach is a beach located in Pecatu Village, South Kuta, Bali. This beach has the potential to be developed to attract both local and foreign tourists, especially architecture. This paper discusses the behavioral architecture approach to obtain the data needed for the development of Nyang Nyang Beach. In the application of Behavioral Architecture, there are various types of mapping that can be done to obtain factual data in creating a design that is responsive and on target. The mapping is in the form of 1) Mapping behavior based on place, 2) Mapping behavior based on individuals, 3) Cognitive mapping, 4) Mapping with semantic differences or interview techniques. The results in the form of design proposals obtained based on problem analysis based on behavioral architecture theory show that the application of this theory provides a design that is able to accommodate the activities and desires of the actors who are active on Nyang Nyang beach and provide comfort in their activities. Keywords: Behavioral Architecture, Nyang Nyang Beach, local tourists, foreign tourists, response.